Titles as discourse: Naming and framing research agendas as evident in theses titles in 1995–2004 - Bengesai , AV; Goba, BB; Karlsson, J (South African Journal of Higher Education, 2011)
This article examines the discourses of theses titles as postgraduate students name and frame their research. It does this by analysing the discourse, nature and trends of title construction in Master’s and Ph.D. research titles 1995–2004 in all universities in South Africa. The dominant discourses are analysed using Foucault’s approach to discourse analysis in order to interrogate their role in the framing of research. What emerges from this discourse analysis is that postgraduate students in our survey use a variety of linguistic devices to frame their research agendas. Also revealing is the fact that most of the frames used draw on assumptions available in research literature and in the Foucauldian sense are thus framed by the powerful institutions, in this sense, authors of research guides. The implications of how discourses are used in the naming and framing of research is discussed.